THE IMPORTANCE OF USING INTERDISCIPLINARY INTEGRATION IN FORMATION OF STUDENTS’ KNOWLEDGE AND SKILLS - Karimov, Sakhob (Журнал иностранных языков и лингвистики, 2023)
This article shows ways to organize music lessons in 5-7 grades based on the content of topics on interdisciplinary organization of music lessons in middle grades.